Determinants of Food Insecurity During COVID-19 Pandemic in Nigeria: A Random Effects Ordered Probit Approach : Array - Oyekale, Tolulope Olayemi; Oyekale, Abayomi (Acta Universitatis Danubius. Œconomica, 2021)
COVID-19 is reversing the global development progresses already attained over the past few decades. Attainment of zero hunger in the Sustainable Development Goals (SDGs) is being threatened and comprehensive approach in managing the pandemic is required. This paper analyzed the determinants of food insecurity status during COVID-19 pandemic in Nigeria. The data were the second, fourth and seventh rounds of COVID-19 National Longitudinal Phone Survey (NLPS) that were carried out in June, August and November 2020 respectively. Food insecurity status was computed with questions on Food Insecurity Experience Scale (FIES) and analyzed with Random Effects Ordered Probit Regression. The results showed that food security improved from 12.19% in June to 24.65% in November. There was a decline in the percentage of severely food insecure households in urban areas from 54.67% in June to 44.53% in November while that in rural areas declined from 60.69% in June to 45.34% in November. The Panel Probit regression showed presence of significant heterogeneity across the panels. Also, age, household size, male, tertiary education, North West residence, public administrator, business or traders and construction job showed statistical significance (p<0.05) with negative sign, while social assistance (p<0.05) has positive sign. Nonperception of COVID-19 risk based on morbidity tendency and financial impacts significantly reduced food insecurity (p<0.01). It was concluded that interventions to address COVID-19 pandemic must critically evaluate their welfare impacts given absence of effective social assistance and must take cognizance of households’ vulnerability to hunger with focus on female headed households, illiterates, unemployed and youths.